1996
DOI: 10.1046/j.1365-2567.1996.d01-758.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils are involved in the non‐specific resistance to listeriosis induced by mycobacterial infections

Abstract: A major role has been recently ascribed to the neutrophil in the resistance to infection by Listeria monocytogenes (L. monocytogenes). Here we evaluated whether such neutrophils played a role in the non‐specific resistance to listeriosis that develops in hosts infected by mycobacteria. We found that the depletion of neutrophils completely abrogated the resistance conferred by the activated macrophages induced during the mycobacterial infection. The lack of killing by activated Kupffer cells and the visualizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Increases in immature and mature MA and neutrophil numbers within 5-21 days are observed in animals treated with BCG or P. acnes [9,42]. Our unpublished studies have also shown that depletion of RB6-8C5 ϩ cells by a specific antibody on Day 14 in HK-BCG mice results in unchanged F4/80 ϩ red pulp MA numbers as well as PGE 2 release (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…Increases in immature and mature MA and neutrophil numbers within 5-21 days are observed in animals treated with BCG or P. acnes [9,42]. Our unpublished studies have also shown that depletion of RB6-8C5 ϩ cells by a specific antibody on Day 14 in HK-BCG mice results in unchanged F4/80 ϩ red pulp MA numbers as well as PGE 2 release (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…In addition to microbicidal activity, PMN are capable of producing several cytokines. In recent years, neutrophils have been shown to produce cytokines such as TNF‐α and IL‐12 after stimulation with bacterial lipopolysaccharides (LPS) and after infection with Candida albicans or Toxoplasma gondii [34–37]. Nakajima et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to microbicidal activity, PMN are capable of producing several cytokines. In recent years, neutrophils have been shown to produce cytokines such as TNF-a and IL-12 after stimulation with bacterial lipopolysaccharides (LPS) and after infection with Candida albicans or Toxoplasma gondii [34][35][36][37]. Nakajima et al [38] observe that normal human peripheral blood eosinophils can transcribe mRNA for a wide variety of cytokines, including TNF-a, IL-4, IL-5, IL-10 and IFN-g.…”
Section: Introductionmentioning
confidence: 99%
“…Live BCG induces not only host resistance to M. tuberculosis but also tumoricidal activity and has been used widely for treatment of superficial bladder cancer [40,41]. Live BCG also induces a nonspecific MA microbicidal activity against Listeria monocytogenes [42,43] and Toxoplasma gondii [44]. It has been reported that a low dose (0.01 mg) of HK-BCG suspended in saline induced a Th1 lymphocyte response against mycobacteria, but the effects were not sufficient to protect against mycobacterial infections, whereas immunization with HK-mycobacteria in mineral oil (CFA) was protective [45].…”
Section: Discussionmentioning
confidence: 99%